Le concept de résilience à l’épreuve du génie urbain - Bruno Barroca; Damien Serre; Diab Youssef (VertigO)
Every natural event impacting urban territories reveals the limits of present risk management strategies and shows the prominent role played by technical networks in crisis and post-crisis management. By means of a transversal approach, urban engineering can be used for analysing technical constraints that lead to the way networks are designed and managed, on the one hand, and to including these networks into territories and habits, on the other. In this way, a network goes beyond being just an object devoted to helping urban activities operate and it becomes a part of a set of inter-related elements, whose operation is similar to that of a technical system. For understanding and analysing urban risks of a natural or technological nature applied to technical systems, using the resilience concept enables us to go beyond technical networks’ reliability objectives, which are often sector-based. Resilience is a recent concept in territorial sciences. The concept is generally applied to systems and deals with risks by the adapting issues at stake, absorbing hazards and the making the territory recover after the crisis. To be able to tackle resilience, urban engineering must redefine the way in which it handles the relations between risks and technical systems and endow itself with a reference tool. This article presents a conceptual model of resilience for technical systems based on identifying three complementary types of resilience. Functional resilience represents a technical system’s capacity to protect itself from important damage and at least provide the service needed for critical infrastructures to operate at the same time. Through functional resilience, technical systems intrinsically endeavour to increase their own resilience. Correlative resilience characterises the relation between service requirements and the technical system’s capacity to fulfil these requirements. Reducing the demand made on a system may enable it to be kept in operation and be protected so that it can recover more rapidly. This means adapting demand to technical systems’ capacity. Over and above the crisis and its management, the return to a “viable” situation is also an element for assessing resilience. Interdependence relations between technical systems and other territories may also form a resilience factor in technical systems. Territorial resilience expresses the capacity to mobilize a territory outside the area impacted.